Active surveillance for antibodies confirms circulation of lyssaviruses in Palearctic bats - Seidlova, Veronika; Zukal, Jan; Brichta, Jiri; Anisimov, Nikolay; Apoznański, Grzegorz; Bandouchova, Hana; Bartonička, Tomáš; Berková, Hana; Botvinkin, Alexander D; Heger, Tomas; Dundarova, Heliana; Kokurewicz, Tomasz; et al. (BMC veterinary research, 2020)
BACKGROUND: Palearctic bats host a diversity of lyssaviruses, though not the classical rabies virus (RABV). As surveillance for bat rabies over the Palearctic area covering Central and Eastern Europe and Siberian regions of Russia has been irregular, we lack data on geographic and seasonal patterns of the infection. RESULTS: To address this, we undertook serological testing, using non-lethally sampled blood, on 1027 bats of 25 species in Bulgaria, the Czech Republic, Poland, Russia and Slovenia between 2014 and 2018. The indirect enzyme-linked immunosorbent assay (ELISA) detected rabies virus anti-glycoprotein antibodies in 33 bats, giving an overall seroprevalence of 3.2%. Bat species exceeding the seroconversion threshold included Myotis blythii, Myotis gracilis, Myotis petax, Myotis myotis, Murina hilgendorfi, Rhinolophus ferrumequinum and Vespertilio murinus. While Myotis species (84.8%) and adult females (48.5%) dominated in seropositive bats, juveniles of both sexes showed no difference in seroprevalence. Higher numbers tested positive when sampled during the active season (10.5%), as compared with the hibernation period (0.9%). Bat rabies seroprevalence was significantly higher in natural habitats (4.0%) compared with synanthropic roosts (1.2%). Importantly, in 2018, we recorded 73.1% seroprevalence in a cave containing a M. blythii maternity colony in the Altai Krai of Russia. CONCLUSIONS: Identification of such "hotspots" of non-RABV lyssavirus circulation not only provides important information for public health protection, it can also guide research activities aimed at more in-depth bat rabies studies.
Keywords: seroprevalence; Ecosystem; Caves; Female; séroepidemiologické studie; zvířata; Europe; roční období; ženské pohlaví; Male; Rhabdoviridae Infections; Seasons; Rusko; Siberia; protilátky virové; Russia; Antibodies, Viral; Animals; infekce viry z čeledi Rhabdoviridae; mužské pohlaví; Chiroptera; Lyssavirus; jeskyně; Evropa; rabies; Seroepidemiologic Studies; ekosystém; blood samples